Why information literacy competencies are key skills for future Portuguese librarians - Sanches, Tatiana (2017)
Social changes regarding the forms of relationship between producer and consumer of information, between author and spectator, or between writer and reader, only to name a few examples, shook certain beliefs concerning the way the production, exchange and reception of information is currently carried and covers multidirectional paths. In this sense, further reflection is necessary on librarians’ competencies and, more specifically, on the emerging need for their training in information competencies. In fact, a change is already visible in librarians’ training in Portugal, namely in the curricular reconfiguration of the training offer which grants a master’s and doctor’s degree in the fields of information and documentation. This study wishes to understand the state of the art of higher education courses in Portugal to train these professionals, currently recognizing the technological axis and information literacy as two sides of a new expression and reconfiguration of this training. The purpose of this paper is to observe this change, using a systematic literature review, urging towards a change in professionals’ attitude regarding their occupation. The goal is thus to reflect about future librarians’ training, focusing on training in information literacy, which will influence their professional practices.